2023
DOI: 10.1111/jfpe.14297
|View full text |Cite
|
Sign up to set email alerts
|

Controlled atmosphere maintains the quality of certain fresh produce in mixed cargo shipments

Abstract: Shipping containers are used globally for the domestic distribution and export of several products. In this study, we compared the efficacy of controlled atmosphere (CA) containers to reefer containers based on the quality of 41 fresh fruits and vegetables exported from Japan to Singapore. We used instrumental analysis and sensory evaluation to compare the quality of fruits and vegetables transported in these two container types. Thirteen types of produce showed higher quality in the CA container than in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The studies in the first group are within the scope of IoT (Haass et al, 2015; Ikegaya et al, 2023; Jedermann et al, 2013; Lütjen et al, 2013; Mees et al, 2018) and RFID (Bollen et al, 2015; Ji & Han, 2012; Tatiana Jiménez‐Ariza et al, 2015). In this respect, studies have been conducted based on designing smart containers that will enable them to have the ability to monitor and control container information remotely over the internet or on the ship's computer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies in the first group are within the scope of IoT (Haass et al, 2015; Ikegaya et al, 2023; Jedermann et al, 2013; Lütjen et al, 2013; Mees et al, 2018) and RFID (Bollen et al, 2015; Ji & Han, 2012; Tatiana Jiménez‐Ariza et al, 2015). In this respect, studies have been conducted based on designing smart containers that will enable them to have the ability to monitor and control container information remotely over the internet or on the ship's computer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, with the rapid development of technology and the economy, people have gradually changed from eating enough to eating well . The nutrient-rich fruits and vegetables have become an essential part of modern people’s diet, , while the storage and preservation of fruits and vegetables have also become a popular research topic. , Recent surveys showed that each year, a large number of fruits and vegetables decay due to improper storage, , resulting in huge economic losses. , After harvesting, fruits and vegetables are subjected to anaerobic respiration inside the tissues in a high CO 2 , low O 2 gas environment, low temperature, or long-term storage process, which in turn produces the metabolite ethanol. , However, excessive accumulation of ethanol can lead to off-flavors, accelerated aging, deterioration in quality, and a significant reduction in storability . Moreover, trace amounts of alcohol fermentation are carried out in pickled fruit and vegetable products, and it is important to be aware of the alcohol content in them when studying the problem of vegetable pickling .…”
mentioning
confidence: 99%
“…1 The nutrient-rich fruits and vegetables have become an essential part of modern people's diet, 2,3 while the storage and preservation of fruits and vegetables have also become a popular research topic. 4,5 Recent surveys showed that each year, a large number of fruits and vegetables decay due to improper storage, 6,7 resulting in huge economic losses. 8,9 After harvesting, fruits and vegetables are subjected to anaerobic respiration inside the tissues in a high CO 2 , low O 2 gas environment, low temperature, or longterm storage process, which in turn produces the metabolite ethanol.…”
mentioning
confidence: 99%